THE EFFECT OF SERVICE QUALITY, CUSTOMER RELATIONSHIP MARKETING, AND BRAND IMAGE ON CUSTOMER LOYALTY AND CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Windiari, Ilham; Djumarno, Djumarno (Dinasti International Journal of Economics, Finance & Accounting, 2021)
Nowadays, intense competition does not only occur in the economic sector, but also penetrates the education sector. There is an analysis gap between information system services, the role of customer relations, and the image of the institution that has not been recognized, has an impact on student satisfaction, as well as the alleged decline in new students based on student and family recommendations. With the consideration of service quality, strategies to build relationships with customers and improve brand image, will determine the level of student satisfaction so as to form student loyalty. This study aims to analyze the effect of Service Quality, Customer Relationship Marketing and Brand Image on Loyalty with Satisfaction as an intervening variable (case study of Academy Telkom Jakarta). This research is categorized in Explanatory Research, with the method of survey using a questionnaire. The sampling technique used is Probability Sampling for a population of 506 student, and considering 305 respondents with Stratified Random sampling method. The analysis used LISREL 8.70 for Structural Equation Modeling (SEM), with a factor loading of 0.05. The results, concluded that there is a relationship between the SERVQUAL, CRM and BRAND variables with the SATISFACTION and LOYALITY variables. Be concluded that, if service quality, customer relationship marketing and brand image are improved, the level of satisfaction will increase, followed by an increase in consumer loyalty..